2006
DOI: 10.1038/ncb1399
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4 regulates non-canonical Wnt signalling and is essential for convergent and extension movements in Xenopus embryos

Abstract: Early shaping of Xenopus laevis embryos occurs through convergent and extension movements, a process that is driven by intercalation of polarized dorsal mesodermal cells and regulated by non-canonical Wnt signalling. Here, we have identified Xenopus syndecan-4 (xSyn4), a cell-surface transmembrane heparan sulphate proteoglycan. At the gastrula stage, xSyn4 is expressed in the involuting dorsal mesoderm and the anterior neuroectoderm. Later, it is found in the pronephros, branchial arches, brain and tailbud. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
146
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 27 publications
5
146
0
2
Order By: Relevance
“…This may be mediated by an effect of Dvl on vesicle trafficking, which has been reported previously in the context of the PCP pathway (8). A mechanism directing Dvl localization to the plasma membrane, such as the one exerted by Syndecan-4 during convergent and extension movements in Xenopus embryos (29), could be also involved.…”
Section: Resultsmentioning
confidence: 98%
“…This may be mediated by an effect of Dvl on vesicle trafficking, which has been reported previously in the context of the PCP pathway (8). A mechanism directing Dvl localization to the plasma membrane, such as the one exerted by Syndecan-4 during convergent and extension movements in Xenopus embryos (29), could be also involved.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, Syndecan-4 and Glypican-4 are both essential for convergent extension, another important form of cell movement during gastrulation. Syndecan-4 also plays a role in the directional migration of neural crest cells (45,46,52). In these cases, Syndecan-4 and Glypican-4 act by regulating the planar cell polarity (PCP) pathway, which is involved in polarized matrix deposition during convergent extension (53).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of the PDGF-AA interaction with fibronectin will be important to consider as the kinetics of binding and release from the matrix may ultimately be responsible for controlling cell activation. The native HSPGs involved in this process are not known and require further investigation, however, several HSPGs are expressed in Xenopus embryos in tissue specific patterns during gastrulation including Syndecans-1 and -2 [expressed in the ectoderm (44)] and Syndecan-4, Glypican-4, and Biglycan [expressed in the ectoderm and mesoderm (44)(45)(46)(47)]. Although the role(s) of these HSPGs in mesendoderm migration have not been investigated, they are involved in a wide range of processes that involve cell rearrangements including embryonic development, wound healing, angiogenesis, neuronal cell migration and cancer cell invasion through their interactions with ECM molecules, growth factors, cytokines, and chemokines (38,(48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is well established in Xenopus, zebrafish and chick embryos that the migration of mesodermal cells during gastrulation requires PCP signaling. [27][28][29] It has also been shown that gastrulation in Xenopus 20 and in zebrafish (unpublished observations) requires the activity of syndecan-4. Thus, it is expected that cell polarity established during the migration of mesodermal cells will be dependent on small GTPases controlled by non-canonical Wnt signaling and syndecan-4.…”
mentioning
confidence: 99%
“…9 Recently this role has also been extended to zebrafish where directional migration of neural crest is severely disrupted in the PCP mutant trilobite (strabismus) and in embryos injected with a dominant negative form of Dsh or a morpholino against wnt5a, 10 with no effect in neural crest cell motility. 9,10 Two factors, pescadillo and syndecan-4 that have recently been proposed as modulators of the PCP signaling, 20,21 are also required for NC migration. 10,21 Taken together, these data point to an essential role for PCP signaling in neural crest migration.…”
mentioning
confidence: 99%